Public relations campaign strategy PT. Pelindo 1 in socializing the Porting Business - Wahyudi, Denny; Adhani, Abrar (COMMICAST, 2021)
PT. Pelabuhan Indonesia I (Persero) is a corporation engaged in the maritime and port sector under the auspices of the Ministry of State-Owned Enterprises (BUMN) headquartered in Belawan, North Sumatra. As a corporation, of course, a campaign is required to inform the business being run so that it is more widely known by the public. As a form of public relations campaign and an effort to socialize its business, Pelindo 1 offers Port Visit activities as a means of learning about the world of ports. This research was conducted to find out how PT Pelindo 1's Public Relations Campaign Strategy in Disseminating its Port Business through the Port Visit program. In this research, it focuses on Port Visit activities with PERHUMAS Muda Medan which was held on February 28, 2020. The type of research that the writer does is descriptive qualitative. In this study, the authors used the theory of Corporate Campaign Theory and AIDDA theory as the basis for campaign marketing. By using the direct observation method where the author participates in the concept-making process and organizing activities as well as the interview method with 5 (five) resource persons, 2 (two) of whom are the Pelindo 1 public relations team, and 3 (three) others are activity participants. The result of this research is that Pelindo 1's PR has made the Port Visit activity a superior program and campaign tool to socialize port business to the community. This is evidenced by the fact that Port visits are registered in the company's Monthly Activity Plan (RKB) and are carried out routinely 2-3 times in a few months. Based on the results of the research, the participants who took part in the Port Visit activity admitted that the concept was not only theoretical but involved directly in the field to see the port area, as well as a fun session as an evaluation stage, making their thinking about the world of the ports and the role and function of ports change not only as a place leaning on ships but serving as a gateway to the world economy.